The Role of Accounting Practices in Advancing the Agenda of Green Finance and Impact Investing - Fakdawer, Nuh. Saneraro (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores the role of accounting practices—Environmental Management Accounting (EMA), social accounting, and integrated reporting—in promoting sustainability and responsible investment. It aims to assess how these practices drive environmentally accountable decisions, enhance resource efficiency, and strengthen stakeholder engagement. Research Design and Methodology: A qualitative literature review methodology is used to analyze and synthesize findings from existing empirical studies and theoretical frameworks. The study draws from diverse sources to understand the impact of accounting approaches on corporate performance, stakeholder relationships, and long-term value creation. Findings and Discussion: The review reveals that standardized methods, data accuracy, and cross-disciplinary collaboration are critical to improving environmental and social impact measurement. Furthermore, the study highlights the growing influence of emerging technologies, including blockchain and artificial intelligence, in enhancing transparency and effectiveness in sustainability reporting. Implications: Findings suggest that accounting practices can play a transformative role in advancing sustainable development and responsible investment. The study provides insights for refining reporting frameworks and underscores the need for additional research on integrating technological innovations into sustainability accounting, thereby supporting informed policy and strategic decision-making.